Cost-effective biodiversity protection through multiuse-conservation landscapes - Peura, Maiju; Eyvindson, Kyle; Burgas, Daniel; Mönkkönen, Mikko; Raatikainen, Kaisa J.; Kotiaho, Janne S. (Springer Science and Business Media LLC, 2024)
Context Intensive land use and exploitation of natural resources are the main direct drivers of biodiversity loss. Transformative changes in land management are called for as conservation and management actions have not been sufficient to support the viability of species populations. It has been proposed that to solve the sufficiency problem one could segregate the landscape into an intensively managed part, and into so-called multiuse-conservation landscapes that aggregate set asides with managed areas for multiple uses. Objectives We describe a scenario analysis where we evaluate the effects and cost-efficiency of transforming the boreal forest from intensively managed production landscapes progressively towards multiuse-conservation landscapes. Methods We simulated Finnish boreal forests under various managements and optimized management to produce six scenarios to reveal the ecological, economic, climate and management regime implications of multiuse-conservation landscapes. Ecological effects explored included habitat availability and metacommunity capacity of dead wood dependent species. Results Increasing the area of set aside and multiuse management increased the habitat availability and metacommunity capacity as well as climate benefits but caused economic losses in terms of timber revenues. Pooling the set asides and multiuse management areas together into the same landscapes reduced the economic losses, had negligible added climate benefits and produced mixed biodiversity effects: pooling decreased habitat availability but increased metacommunity capacity across all landscapes. Conclusions Changing land management and aggregating conservation efforts can be a cost-efficient way to protect biodiversity. Our results suggest biodiversity benefits in landscapes where the set aside and multiuse is aggregated. Careful spatial planning can also alleviate the conflicts between ecological and economic values of land.
Keywords: Biodiversity loss; Connectivity; Forestry; Land sharing; Land sparing; Population ecology; Spatial planning